2007
DOI: 10.1103/physrevc.75.064607
|View full text |Cite
|
Sign up to set email alerts
|

Improved di-neutron cluster model forHe6scattering

Abstract: The structure of the three-body Borromean nucleus 6 He is approximated by a two-body di-neutron cluster model. The binding energy of the 2n-α system is determined to obtain a correct description of the 2n-α coordinate, as given by a realistic three-body model calculation. The model is applied to describe the breakup effects in elastic scattering of 6 He on several targets, for which experimental data exist. We show that an adequate description of the di-neutron-core degree of freedom permits a fairly accurate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(144 citation statements)
references
References 32 publications
(25 reference statements)
7
131
1
4
Order By: Relevance
“…The CDCC calculations presented here for 27 MeV repeat exactly those of Moro et al [4] for 6 He + 208 Pb. The same 2n + α binding potentials and 2n + 208 Pb and α + 208 Pb optical potentials were employed, along with an identical binning scheme for the 2n + α continuum of 6 He.…”
Section: B the Cdcc Calculationssupporting
confidence: 70%
See 3 more Smart Citations
“…The CDCC calculations presented here for 27 MeV repeat exactly those of Moro et al [4] for 6 He + 208 Pb. The same 2n + α binding potentials and 2n + 208 Pb and α + 208 Pb optical potentials were employed, along with an identical binning scheme for the 2n + α continuum of 6 He.…”
Section: B the Cdcc Calculationssupporting
confidence: 70%
“…Moro et al [4] developed a two-body 2n-α cluster model (hereafter, Moro-model) of 6 He specifically for application to the scattering of this nucleus from high-Z nuclei such as 208 Pb. The parameters of the two-body model were chosen to reproduce relevant properties of a three-body model.…”
Section: A the Model Of Moro Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Previous CDCC calculations for the reactions studied in this work [16,44,52] have shown that using these partial waves is sufficient to obtain converged results and to describe satisfactorily the existing data for such reactions. We did not attempt to include higher partial waves, since this would make the calculations very demanding computationally.…”
Section: Application To Reactionsmentioning
confidence: 99%